Landscape morphology analysis a basis for redevelopment of the public plazas in Manila - Andalecio, Melba Nabuya (Quezon City College of Architecture, University of the Philippines Diliman, 2007)
Urban and town planning in the Philippines have traces of the rich landscape heritage that made the country a unique region. The public plaza is one of which has been the setting of religious, social and political life for most of the Filipinos in the last 400 years. Its existence is highly regarded by the community as an integral space of the poblacion and town centers. Its strategic location is vital in the planning of our towns and cities where the activities of the people are inherent tied to it. Norma Alarcon strengthened this when she quoted "No Filipino community is complete without one (plaza)". (2003). In the country, Manila is one of the cities that is endowned with a number of public plazas. The public plaza is characterized and structured by different development patterns and evolved into various visages. Landscape morphology of the Public Plaza has physical changes brought about by certain needs such as giving way to the pressures of traffic resulting to size erosion and reshaping, cultural compromises in favor of some developments especially shopping malls, and habitat for the homeless making the place uncomfortable and scary. This is actually true with most of the Public Plazas in Manila. The transformation of Public Plaza is inevitable due to the changing needs of society with time. This does not mean however, that any forced transformations can just be done to the plaza indiscriminately. It is believed that while it has its own existence and identity, it should also respond to the needs of the community for a communal space. This study analyzes the selected public plazas in Manila in terms of their landscape morphologies as tools in formulating guidelines for redevelopment. The study is limited on certain areas of Landscape Morphology because of the broadness of the subject and limited time and resources available for the research work. These areas include (1) forms and arrangement (2) elements and (3) scale and proportion (see definition of terms in chapter 2). It also includes historical background, existing policies, type of users and use of space.
Vita.
Thesis (Master of Tropical Landscape Architecture)--University of the Philippines, Diliman.
Keywords: Landscape design -- Manila; City planning -- Manila; Manila -- Plaza